Problem of Value in I. Kant’s Ethics - Anilionytė, Loreta (Problemos, 1990)
I. Kant’s ethics of obligation when compared to the descriptive ethic of Modem time presented by itself a real revolution in the field. Nevertheless, many principles of the philosophy of Modem time were inherited without any change, namely, the conception of the two powers of man – that of sensibility and that of rationality. According to I. Kant, all human acts of sensual origin are to be considered as indifferent, and only those of rational origin do have moral value. Because of the gnoseological approach to the problem of morality, the content of moral was taken away as unnecessary, and the highest moral law has taken the form of pure law.